Circular RNA SMO sponges miR-338-3p to promote the growth of glioma by enhancing the expression of SMO - Xiong, Zhiyong (Aging (Albany NY), 2019)
Glioma is one of the most common tumors in the brain and complete cure still a challenge. The present research aimed to investigate the molecular mechanism of circular RNA SMO (circSMO742) in glioma, via targeting miR-338-3p and regulating SMO expression. QRT-PCR was utilized to examine the expression profiles of circSMO742 and microRNA-338-3p (miR-338-3p) in glioma. SMO protein in glioma was tested via western blot. RNA pulldown assay and dual luciferase reporter assays were used to explore the targeting correlation between RNAs. MTT assay, transwell assays and flow cytometry were used to investigate cell proliferation, migration and invasion, and apoptosis, respectively. Tumor xenograft was done to ascertain the effect of circSMO742 knocking down on tumor growth. CircSMO742 and SMO were highly expressed in glioma tissues, while miR-338-3p expression was reduced. CircSMO742 together with SMO could promote cells proliferation, migration and invasion while inhibit cells apoptosis, whereas miR-338-3p showed negative impacts on the cell activity. Knocking down of circSMO742 suppressed glioma growing in vivo. CircSMO742 promoted glioma growth by sponging miR-338-3p to regulate SMO expression. Our research revealed a new molecular mechanism of glioma growth and provide a fresh perspective on circRNAs in glioma progression.